2022
DOI: 10.58753/jbspust.03.01.2022.02
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Celebrity Endorsement on Young Consumer Purchase Intention in Bangladesh: An Empirical Study

Abstract: Purpose: The purpose of this study is to investigate the effect of celebrity endorsement components (expertise, attractiveness, and trustworthiness) on brand attitude, brand loyalty, and purchase intention. This study looks at the elements of celebrity endorsements that influence young consumers' purchasing preferences in the Barishal region of Bangladesh. Methodology: The study model incorporates constructs from earlier literature that have been proven to have substantial relations with purchasing intention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Studies such as Khan (2018), Zipporah & Mberia (2014, and Ahmed et al (2015) emphasize the importance of carefully selecting the right celebrity endorser to effectively communicate brand messages and elicit positive responses from consumers. In regions like Karachi, Pakistan (Khan, 2018), andHo Chi Minh City, Vietnam (Minh Ha &Hung Lam, 2016), researchers have found that factors such as celebrity-brand congruence, trustworthiness, and expertise play crucial roles in shaping consumer attitudes and purchase intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies such as Khan (2018), Zipporah & Mberia (2014, and Ahmed et al (2015) emphasize the importance of carefully selecting the right celebrity endorser to effectively communicate brand messages and elicit positive responses from consumers. In regions like Karachi, Pakistan (Khan, 2018), andHo Chi Minh City, Vietnam (Minh Ha &Hung Lam, 2016), researchers have found that factors such as celebrity-brand congruence, trustworthiness, and expertise play crucial roles in shaping consumer attitudes and purchase intentions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For instance, a potential consumer who is searching for information about a certain product, when he sees an advertisement that includes his loveable celebrity endorsing that specific product, subconsciously he will form a positive impression about this particular brand Following this step directly is evaluation of alternatives. This is the most critical stage in which a brand can construct a solid competitive edge through using celebrities' endorsements (Khan, Rukhsar, & Shoaib, 2016).…”
Section: Celebrity Endorsementmentioning
confidence: 99%